INTEGRATION OF GREEN SUKUK AND CASH WAQF LINKED SUKUK FOR FINANCING AGRICULTURE SUSTAINABLE - Annisa Nur Salam; Iskandar Iskandar (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2021)
Abstract: Green sukuk has an underlying form of environmental preservation activities and is a form of Indonesia's commitment to addressing the impacts of climate change. The Cash Waqf Linked Sukuk (CWLS) is a cash waqf investment in SBSN where the imbalance is channeled to social activities including social infrastructure which is a waqf asset. Based on the two-state sukuk innovations, in general, this research intends to integrate the implementation of green sukuk and CWLS in sustainability. The method used in this research is a qualitative approach with descriptive analysis. The results of this study are the proposed Green CWLS model for financing the agricultural sector. This innovation will be a breakthrough in funding to reduce climate change as well as providing opportunities for Muslims who wish to invest socially, especially in the agricultural sector. Based on the contract used, green sukuk can use ijarah, murabahah, salam, ishtisna`, mudharabah and musyarakah contracts. While CWLS uses a wakalah contract. The hope is that this can become a new recommendation for policymakers such as the Ministry of Finance, the Indonesian Waqf Agency , the Ministry of Religion, and Bank Indonesia in advancing fiscal finance while trying to balance economic and environmental impacts which are currently the focus of all countries. In addition, this model also supports the agricultural sector to improve the welfare of local farmers and ensure food security and security for the people of Indonesia.